Implications of nighttime temperature on metamitron impacts on the photosynthetic machinery functioning of Malus x domestica Borkh - Rosa, Nídia (2021)
Metamitron (MET) is a fruitlet thinning compound for apple trees, needing better understanding of its action on leaf energy metabolism, depending on nighttime temperature. A trial under environmental controlled conditions was set with ‘Golden Reinders’ potted trees, under 25/7.5 and 25/15 ◦C (diurnal/nighttime temperature), with (MET, 247.5 ppm) or without (CTR) application, and considering the monitoring of photosynthetic and respiration components from day 1 (D1) to 14 (D14). Net photosynthesis (Pn) decline promoted by MET after D1 was not stomatal related. Instead, non-stomatal constraints, reflected on the photosynthetic capacity (Amax), included a clear photosystem (PS) II inhibition (but barely of PSI), as shown by severe reductions in thylakoid electron transport at PSII level, maximal (Fv/Fm) and actual (Fv’/Fm’) PSII photochemical efficiencies, estimate of quantum yield of linear electron transport (Y(II)), and the rise in PSII photoinhibition status (Fs/Fm’ and PIChr) and uncontrolled energy dissipation (Y(NO)). To Pn inhibition also contributed the impact in RuBisCO along the entire experiment, regardless of night temperature, here reported for the first time. Globally, MET impact on the photosynthetic parameters was usually greater under 7.5 ◦C, with maximal impacts between D4 and D7, probably associated to a less active metabolism at lower temperature. Cellular energy metabolism was further impaired under 7.5 ◦C, through moderate inhibition of NADH-dependent malate dehydrogenase (MDH) and pyruvate kinase (PK) enzymes involved in respiration, in contrast with the increase of dark respiration in MET 7.5 until D7. The lower impact on PK and MDH under 15 ◦C and a likely global higher active metabolism at that temperature would agree with the lowest sucrose levels in MET 15 at D4 and D7. Our findings showed that MET alters the cell energy machinery in a temperature dependent manner, affecting the sucrose balance mainly at 15 ◦C, justifying the observed greater thinning potential